Conformity to Masculine Gender Norms Inventory in the Spanish population - Cuéllar Flores, Isabel; Sánchez López, María del Pilar; Dresch, Virginia (Anales de Psicología / Annals of Psychology, 2010)
The administration of the Conformity to Masculine Norms Inventory - CMNI (Mahalik et al., 2003) in a group of Spanish men is described. The CMNI was designed to assess, from a multidimensional perspective, men's degree of conformity to a series of gender norms identified in the dominant culture of the United States of America. The questionnaire was administered to 727 men between 18 and 83 years of age with a mean age of 30.17 (S. D. 12.14), with diverse educational levels and heterogeneous work situations and who came from various regions of Spain. The reliability data are mostly satisfactory, and the correlation matrix between the subscales confirms Mahalik's (2000) theoretical model. The differences between the results obtained in the Spanish group and the American group suggest the effect of cultural factors. Factor analysis revealed a structure characterised by the grouping of items similar to the one obtained in the USA and, although it is different in some aspects, in general, it supports the structure proposed by the authors. We suggest regrouping some of the subscales that have been shown to be related in other supraordered subscales with the aim of improving the suitability of the CMNI for use in Spanish population.